(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The article discusses the new directions of language research in modern world language education. Linguistics and ethnolinguistics in Kazakh linguistics have been studied with the formation of new trends. Cumulative measures of language in new linguistic fields are shown by examples.